2017
DOI: 10.1039/c7ta03476h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cryptomelane type α-MnO2(KxMn8O16) cathode materials with tunable K+content: the role of tunnel cation concentration on electrochemistry

Abstract: Here, we synthesized a series of α-MnO2 samples with differing K+ content but similar physical properties allowing direct study of the role of tunnel K+ on the electrochemistry of α-MnO2 cathodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
91
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 76 publications
13
91
1
Order By: Relevance
“…37 However, the effect of tunnel cations on MnO 2 electrochemistry is still debated since lowering the stabilizing ion concentration has also been reported by another group to improve the battery performance of MnO 2 nanostructures. 38 Factors causing such seemingly inconsistent results could be that different methods of cation control and different characterization methods that result in various cation concentration ranges have been used in these associated studies. However, the above-mentioned complication in clarifying the role of tunnel cations makes this material system exceptionally interesting, and we believe more intensive work focusing on reliable cation control and compositional characterization should be devoted in the future to revealing the underlying mechanisms.…”
Section: Moving Toward Tunnel Homogeneitymentioning
confidence: 99%
“…37 However, the effect of tunnel cations on MnO 2 electrochemistry is still debated since lowering the stabilizing ion concentration has also been reported by another group to improve the battery performance of MnO 2 nanostructures. 38 Factors causing such seemingly inconsistent results could be that different methods of cation control and different characterization methods that result in various cation concentration ranges have been used in these associated studies. However, the above-mentioned complication in clarifying the role of tunnel cations makes this material system exceptionally interesting, and we believe more intensive work focusing on reliable cation control and compositional characterization should be devoted in the future to revealing the underlying mechanisms.…”
Section: Moving Toward Tunnel Homogeneitymentioning
confidence: 99%
“…2). Poyraz et al [46] reported that the KxMn8O16 samples with low K + content, K0.32Mn8O16, have a lower decomposition temperature of 510 °C compared to T=580 °C for the samples with high K + content (K0.75Mn8O16). Fig.…”
Section: Elemental and Structural Studiesmentioning
confidence: 99%
“…We pay a special attention to characterize the crystal chemistry of α-type MnO2 prepared from redox reaction of potassium permanganate, which always contains a residual fraction of K + ions in the 2×2 tunnels preserving the structural stability of this material. Note that most of numerous works published in the literature neglect this aspect; only few papers consider the presence of potassium in the cryptomelane framework [44][45][46][47][48][49][50][51]. Two samples were prepared using a redox synthesis…”
Section: Introductionmentioning
confidence: 99%
“…Cryptomelane-type KMn 8 O 16 was synthesized by a modified hydrothermal method (Poyraz et al, 2017). The typical preparation procedure is as follows, 6 mmol of MnSO 4 ·H 2 O and 12 mmol of (NH 4 ) 2 SO 4 and 12 mmol K 2 SO 4 were dissolved in 50 mL of 6 mmol (NH 4 ) 2 S 2 O 8 solution.…”
Section: Methodsmentioning
confidence: 99%
“…One dimensional (1D) tunnel structured cryptomelane type manganese dioxides, Mn 8 O 16 (α-MnO 2 ) as the cathode materials have been received extensive concerns, as they can reversibly host various cations including Li + and K + and so on, of which K x Mn 8 O 16 was previously reported in the fields of catalysis and lithium ion battery (Poyraz et al, 2017). Herein, this study aims to establish the aqueous hybrid battery based on cheap intercalated potassium compound KMn 8 O 16 as the cathode material and zinc as the anode.…”
Section: Introductionmentioning
confidence: 99%